Creating a public : people and press in Meiji Japan - Huffman, James L., 1941- (University of Hawai'i Press, 1997)
"No institution did more to create a modern citizenry than the newspaper press of the Meiji period (1868-1912). Here was a collection of highly diverse, private voices that provided increasing numbers of readers - many millions by the end of the period - with both its fresh picture of the world and a changing sense of its own place in that world. Creating a Public is the first comprehensive history of Japan's early newspaper press to appear in English in more than half a century. Drawing on decades of research in newspaper articles and editorials, journalists' memoirs and essays, government documents and press analyses, it tells the story of Japan's newspaper press from its elitist beginnings just before the fall of the Tokugawa regime through its years as a shaper of a new political system in the 1880s to its emergence as a nationalistic, often sensational, medium early in the twentieth century." "More than an institutional study, this work not only traces the evolution of the press' leading papers, their changing approaches to circulation, news, and advertising, and the personalities of their leading editors; it also examines the interplay between Japan's elite institutions and its rising urban working classes from a wholly new perspective - that of the press. What emerges is the transformation of Japan's commoners (minshu) from uninformed, disconnected subjects to active citizens in the national political process - a modern public. Conversely, minshu begin to play a decisive role in making Japan's newspapers livelier, more sensational, and more influential. As Huffman states in his Introduction: "The newspapers turned the people into citizens; the people turned the papers into mass media."" "In addition to providing new perspectives on Meiji society and political life, Creating a Public addresses themes important to the study of mass media around the world: the conflict between social responsibility and commercialization, the role of the press in spurring national development, the interplay between readers' tastes and editors' principles, the impact of sensationalism on national social and political life. Huffman raises these issues in a comparative context, relating the Meiji press to American and Japanese press systems at similar points of development." "With its broad coverage of the press' role in modernizing Japan, Creating a Public will be of great interest to students of mass media in general as well as specialists of Japanese history."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved